Steady-state visual evoked potentials are unchanged following physical and cognitive exertion paradigms. (November 2021) - Salazar, Sophia; Oyewole, Femi; Obi, Ted; Baron, Rebecca; Mahony, Dylan; Kropelnicki, Anna; Cohen, Adrian; Putrino, David; Fry, Adam
Background: There is a need for objective biomarkers of sports-related concussion that are unaffected by physical and cognitive exertion. Electroencephalography-based biomarkers such as steady-state visually evoked potentials (SSVEPs) have been proposed as one such biomarker. The aim of this study was to investigate the effects of cognitive and physical exertion on SSVEP signal-to-noise ratio (SNR). Methods: This study involved two experiments. The first experiment was performed in a controlled laboratory environment and involved a treadmill run designed to induce physical fatigue and a Stroop task designed to induce mental fatigue, completed in a randomized order on two separate visits. SSVEPs were evoked using a 15-Hz strobe using a Nurochek headset before and after each task. Changes in the 15-Hz SSVEP SNR and self-reported fatigue (visual analog scales) were assessed. In the second experiment, SSVEP SNR was measured before and after real-world boxing matches. Paired t-tests compared pre- and post-task SSVEP SNR and fatigue scores. Results: Eighteen participants were recruited for experiment 1. Following the treadmill run, participants reported higher physical fatigue, mental fatigue, and overall fatigue ( p ≤ 0.005; d ≥ 0.90). Following the Stroop task, participants reported higher mental fatigue and overall fatigue ( p < 0.001; d ≥ 1.16), but not physical fatigue. SSVEP SNR scores were unchanged following either the Stroop task ( p = 0.059) or the treadmill task ( p = 0.590). Seven participants were recruited for experiment 2. SSVEP SNR scores were unchanged following the boxing matches ( p = 0.967). Conclusions: The results of both experiments demonstrate that SSVEP SNR scores were not different following the treadmill run, Stroop task or amateur boxing match. These findings provide preliminary evidence that SSVEP fidelity may not be significantly affected by physical and cognitive exertion paradigms.